The initial appraisal of buried DAS system in CO2CRC Otway Project: the comparison of buried standard fibre-optic and helically wound cables using 2D imaging. Issue 1 (2nd January 2019) - Yavuz, Sinem; Freifeld, Barry; Pevzner, Roman; Dzunic, Aleksandar; Ziramov, Sasha; Bóna, Andrej; Correa, Julia; Tertyshnikov, Konstantin; Urosevic, Milovan; Robertson, Michelle; Daley, Thomas
ABSTRACT: This study aims to assess the ability of shallow distributed acoustic sensing (DAS) to serve as a cost-effective seismic sensor array for permanent monitoring applications. To this end, as part of the CO2CRC seismic monitoring program, a fibre-optic DAS array was deployed alongside a permanently buried geophone array at the Otway Project site (Victoria, Australia). The DAS array consisted of a standard commercially available tactical fibre-optic cable, which was deployed in 0.8 m deep trenches. A custom-designed helically wound (HW) cable was also deployed in one of the DAS trenches for comparison of the cable designs. Simultaneous acquisition of the seismic data was carried out using ∼ 3000 vibroseis source points and geophones, DAS standard and HW cables. For initial assessment of the seismic images acquired with DAS and to compare different cable designs, preliminary 2D seismic reflection processing is conducted on both DAS cables and geophone data along a single 2D line. The geophone data processing guided processing of the DAS data. Several shallow structures (100–450 ms) and some important reflectors at 450–600 ms are observed on the final DAS images. Comparison of the two different DAS cable types demonstrated that seismic imaging would benefit DAS technology. However, the benefit of utilising HW cable is modest compared with the standard cable. The workflows and results of this study pave the way for processing of the 3D seismic data set acquired with the DAS array, as well as further detailed analysis of the DAS cables and the system itself.